Design and optimization of bail-shaped microstrip patch antenna for mid-band 5G application using a lightGBM model - Vijayakumari, G.; Annalakshmi, T. (Institute of Advanced Engineering and Science, 2025)
This study suggests a bail-shaped microstrip patch antenna designed for 5G applications. This antenna model operates in the 3.45 GHz wireless communication frequency range, which is a component of the so-called C-band (3.3 to 4.2 GHz), which is widely utilized for mid-band 5G deployments across the globe. Antenna size optimization is achieved at 31×28 mm2. On the patch, a slot is added to enhance the return loss features. The light gradient boosting machine (LightGBM) model for prediction acts as an objective function of the considered piranha foraging optimization algorithm (PFOA) to adjust the antenna's slot dimension, which will be used to optimize the slot width. In order to get a superior return loss value of around -39.90<-10 dB, the optimization approach that is provided seeks to achieve the ideal slot length. The proposed device exhibits remarkable radiation efficiency by partially grounding, with a peak gain of around 2.535 dBi at 3.45 GHz. A novel hybrid approach combines the LightGBM prediction model with the PFOA to fine-tune slot dimensions, achieving a superior return loss of -39.90 dB. The exclusivity of this effort is the incorporation of machine learning algorithms to attain significantly improved parameters.